Soil erosion and sediment dynamics in the Anthropocene: a review of human impacts during a period of rapid global environmental change - Owens, Philip N. (Journal of soils and sediments, 2020)
Purpose Humanity has been modifying the planet in a measurable way for thousands of years. Recently, this influence has been such that some feel we are in a new geological epoch, the Anthropocene. This review will describe how soil erosion and sediment dynamics have (i) been used to assess the impact of humans on the planet and (ii) affected the global climate and influenced water security. Emphasis is placed on changes since the middle of the twentieth century, as this coincides with what many suggest is the start of the Anthropocene Epoch. Results and discussion The use of sediment archives has been instrumental in our understanding of how environmental systems have developed over time, both naturally and in response to anthropogenic activities. Additional information has come from measurement and monitoring programs, and tracing and fingerprinting studies. In turn, models have been developed that enable forecasting. Some of the main global impacts of enhanced soil erosion and changes in sediment dynamics and sediment composition include: changes in radiative energy balances and impacts on the cryosphere; the global carbon cycle; and greenhouse gas emissions. Impacts on water security include: effects on freshwater biota, including wild salmon populations; fluxes of contaminants, including microplastics; and reservoir and river channel sedimentation, including flooding. Sediment archives and monitoring programs have also been used to document the effect of mitigation measures and environmental policies. Conclusion Sediment archives enable us to assemble information over a variety of timescales (i.e., 10 0 to 10 5 years and longer) and a range of spatial scales (from sub-watershed to continental), in addition to environments ranging from arid to tropical to polar. Often the temporal resolution is better than other paleoenvironmental reconstruction approaches. As such, sedimentary records, when combined with measurement and monitoring approaches and other sources of information, have enabled us to determine changes in atmospheric, terrestrial, and aquatic systems, especially over the last 100 years. While soil erosion and sediment dynamics have provided a wealth of information and greatly enhanced our understanding of the role of humanity in modifying the planet, suggestions are given for further research.